Screening of Indonesian Streptomyces sp. Capable of Secreting Transglutaminase (Mtgase) and Optimization of Mtgase Production Using Different Growth Media - Yusro Nuri Fawzya; Dewi Seswita Zilda; Seprianto Chaniago; Hana Nurullita Prestisia; Puspita Lisdiyanti; Noer Khasanah (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2016)
Transglutaminase (TGase), an enzyme that catalyzes the formation of inter- and intra-molecular e-(l-glutamyl) lysine (GL) crosslinks, plays an important role in surimi-based products production. The development and the diversification of surimi-based products have recently been getting popular in Indonesia. These surimi-based products can be made from various types of fish. These products generally exhibit good gel strength properties,  depending on the fish type and the processing method used. Transglutaminase plays an important role in generating such properties. Fish’s endogenous TGase reduces quickly after it is caught and is almost completely destroyed by freezing it, applying exogenous TGase may improve fish’s gel forming ability. Microbial transglutaminase (MTGase) can potentially be used to increase gel properties. In this research, a total of 228 Streptomyces strains from marine and terrestrial environments were screened and selected based on their ability to produce MTGase. Strain TTA 02 SDS 14 exhibited the highest activity; and therefore, it was selected for further study. The 16S-rRNA gene analysis showed that it shared 99% similarity to S. thioluteus. In order to optimize MTGase activity, enzyme production was carried out using six different formulas media, designated as media A, B, C, D, E, and F. The result shows that the highest MTGase activity was observed in medium B that contains pepton (1.5%), MgSO4.7H20 (0.1%), KH2PO4 (0.5%), Na2HPO4 (0.5%), soybean powder (2%), potato starch (2%), and glucose (1.5%). The MTGase activity reached the highest level (1.45 U/ml) after 4 days of incubation